2019
DOI: 10.1038/s41598-019-41410-y
|View full text |Cite
|
Sign up to set email alerts
|

Drug-loaded hyaluronic acid hydrogel as a sustained-release regimen with dual effects in early intervention of tendinopathy

Abstract: Resulting from accumulative microtrauma, impaired healing and oxidative stress, tendinopathy is a debilitating and relentlessly deteriorating disease that greatly affects daily function and quality of life. Current therapy usually provides symptomatic relief only. Sufferers undergo repetitive and protracted treatment courses that rarely alter the disease process. We aim to develop a sustained-release regimen with an intrinsic therapeutic effect in tendinopathy treatment, using oxidised hyaluronic acid/adipic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…They demonstrated that antiadhesive properties of HA films or coatings are indeed ideal for bacterial biofilm formation that inherently provide an antibacterial barrier. Hsiao [74] et al developed a sustained-release HA-based hydrogel targeting tendinopathy treatment. They formulated oxidized HA/adipic acid dihydrazide hydrogel encapsulating a drug.…”
Section: Controlled Release Of Antiseptics and Antibiotics From Hamentioning
confidence: 99%
“…They demonstrated that antiadhesive properties of HA films or coatings are indeed ideal for bacterial biofilm formation that inherently provide an antibacterial barrier. Hsiao [74] et al developed a sustained-release HA-based hydrogel targeting tendinopathy treatment. They formulated oxidized HA/adipic acid dihydrazide hydrogel encapsulating a drug.…”
Section: Controlled Release Of Antiseptics and Antibiotics From Hamentioning
confidence: 99%
“…To overcome the problem of dissolution and release of poor drug releasing ability, RGD based cationic polymers have also been reported in the literature 13 . Hence, polymeric encapsulations like scaffolds, hydrogels 14 , nano-carriers and micro-carriers are beneficial to overcome the bottleneck of dissolution and controlled release of hydrophobic drugs [15][16][17] . Encapsulation of hydrophobic drugs into nanofibrous PCL, owing to its potential as drug delivery vehicles, enhances dissolution, whereas its hydrophobic property efficiently modulates rate of water diffusion and leaching out of drugs from these fibers, for sustained long term release 18 .…”
mentioning
confidence: 99%
“…This ability seems to be related to the increased deformability, which avoid vesicle destruction and the consequent leakage of the payload. Sodium hyaluronate is a naturally occurring polysaccharide with restoration and the healing properties 75 . It is widely used in the design of new delivery systems due to its biofunctionality associated to bioadhesive and viscoelastic properties 76,77 .…”
Section: Discussionmentioning
confidence: 99%